Knowledge Construction in Psychiatric Nursing: A Historical-critical Approach - Silva, Teresa Cristina da; Ratner Kirschbaum, Débora Isane (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2010)
The first appearance of nursing in psychiatry was as knowledge subsidiary to medical practice. Such origin offers elements to outline the beginning of a professional identity based on knowledge, which are yet unspecific in psychiatric nursing. It is only in the 1950s that such knowledge would become formal and systemized, a moment associated with the first theorizations of psychiatric nursing practice. The objective of this article is to reflect on the specificity of psychiatric nursing knowledge from an historical-critical perspective. It is a reflection about a literature review on psychiatric nursing knowledge (performed on Medline and Cinahl databases) using a fictional clinical setting as the strategy for analysis. The analyses are founded on the Lacans elaborations on science, knowledge and his theorization of discourses as well as the analysis used by Almeida and Rocha about nursing knowledge. Hence, we analyzed two aspects of psychiatric nursing knowledge: one formal and systematized, and another informal, non-systematized and in the scientific standards, both determining and/or influencing psychiatric nursing practice since the beginning. We reflected on the improvements that were achieved, but also on the effects from denying knowledge specific to nursing. In view of the numerous published studies and reflections, there is consensus on the urgency to build new knowledge and practice. We have a firm belief on the pertinence, relevance and urgency of addressing our specific knowledge acknowledging our masters, questioning them in the search for answers to new questions, based on questions made by the subject who suffers.